2020
DOI: 10.3390/genes11080905
|View full text |Cite
|
Sign up to set email alerts
|

The Prospective Study of Epigenetic Regulatory Profiles in Sport and Exercise Monitored Through Chromosome Conformation Signatures

Abstract: The integration of genetic and environmental factors that regulate the gene expression patterns associated with exercise adaptation is mediated by epigenetic mechanisms. The organisation of the human genome within three-dimensional space, known as chromosome conformation, has recently been shown as a dynamic epigenetic regulator of gene expression, facilitating the interaction of distal genomic regions due to tight and regulated packaging of chromosomes in the cell nucleus. Technological advances in the study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 101 publications
(158 reference statements)
0
12
0
Order By: Relevance
“…Indeed, it has been shown that epigenetic markers of training adaptation are retained in skeletal muscle even after periods of detraining [ 21 , 22 ], suggesting that epigenetic mechanisms underpin an intrinsic ability of the human body to “memorize” training adaptations. Recently, a new class of epigenetic marker known as the chromosome conformation signature has yielded promising results in medical research and may also be used to investigate whether changes in genome conformation (organization of the genome within three-dimensional nuclear space) are involved in regulating exercise responsiveness [ 23 ]. Whilst technological advances continue to assist in the discovery of new biomarkers relating to sport and exercise, the ability to maximize favorable aspects of the microbiome, genome, epigenome and other omics factors (e.g., the transcriptome, proteome and metabolome) to positively impact human PPTs relies on the combination of biomarker knowledge and appropriate environmental factors, such as effective training programs and disciplined lifestyle habits.…”
Section: Sports Genomics: Actuality and Prospectsmentioning
confidence: 99%
“…Indeed, it has been shown that epigenetic markers of training adaptation are retained in skeletal muscle even after periods of detraining [ 21 , 22 ], suggesting that epigenetic mechanisms underpin an intrinsic ability of the human body to “memorize” training adaptations. Recently, a new class of epigenetic marker known as the chromosome conformation signature has yielded promising results in medical research and may also be used to investigate whether changes in genome conformation (organization of the genome within three-dimensional nuclear space) are involved in regulating exercise responsiveness [ 23 ]. Whilst technological advances continue to assist in the discovery of new biomarkers relating to sport and exercise, the ability to maximize favorable aspects of the microbiome, genome, epigenome and other omics factors (e.g., the transcriptome, proteome and metabolome) to positively impact human PPTs relies on the combination of biomarker knowledge and appropriate environmental factors, such as effective training programs and disciplined lifestyle habits.…”
Section: Sports Genomics: Actuality and Prospectsmentioning
confidence: 99%
“…Epigenetic factors are modulated by exercise [ 265 ] and may play a protective role in the physiological and cellular responses to viral infection. Epigenetics includes factors that regulate gene expression through histone methylation and acetylation, DNA/RNA methylation, chromatin remodeling, and non-coding RNAs [ 266 ].…”
Section: Effects Of Physical Activity and Exercise On Human Biology In View Of Covid-19mentioning
confidence: 99%
“…However, epigenetic processes do not stop at birth; rather, they continue to be part of the fundamental cell processes during the rest of the life. In recent years, it has been obvious that epigenetic processes are involved in processes like learning (Collins et al, 2019;Kim & Kaang, 2017;Leighton et al, 2018), stress responses (Cao-Lei et al, 2016;Li et al, 2020;Xu et al, 2020), and during physical activity (Hall et al, 2020;Lindholm et al, 2014;Seaborne et al, 2018). Additionally, individuals suffering from different diseases and disorders present changed epigenetic patterns.…”
Section: Epigenetics: An Overviewmentioning
confidence: 99%
“…Thus, environmental signals contribute to decisions about which genes are expressed and thus what happens in our cells and consequently in our whole bodies. Environmental signals entering the body are of a great range of characters, emanating from, for example, stressful situations (Cao-Lei et al, 2016;Li et al, 2020;Xu et al, 2020), food and drink (De Fabiani et al, 2010;Landecker, 2011;Silva et al, 2019), and physical activity (Hall et al, 2020;Lindholm et al, 2014;Seaborne et al, 2018). This insight has great consequences; with the new knowledge of epigenetics, we could claim our ability to control and steer our lives to a higher degree than thought before.…”
Section: Category 1: Epigenetics and Nature Of Sciencementioning
confidence: 99%